Oportunistik Incumbent dalam Penganggaran Pendapatan dan Belanja pada Pemilihan Kepala Daerah Serentak Tahun 2017 - Ariyanto, Dodik; Dewi, Ayu Aryista (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 14 No 1 (2019), 2019)
This study aims to examine the effects of incumbent opportunistic behavior on  budget compilation related to the simultaneous election of regional heads  (pemilukada) in regencies, cities, and provinces in Indonesia in 2017. In addition,  the study also examines differences in incumbent opportunistic behavior when  preparing budgets for elected incumbent heads compared with those who did not  get elected as well as differences in incumbent opportunistic behavior a year prior  to and during the simultaneous elections. The research population comprises all  regencies, cities, and provinces in Indonesia. The sampling method used for this  study was purposive sampling. Data were analyzed using multiple linear  regression and different types of t-Tests. The results of the analysis showed that  PAD and SiLPA had an effect on the incumbent opportunism behavior and DAK  had no effect on incumbent opportunism behavior. The results of different t-Tests  revealed differences in incumbent opportunistic behaviors of winners and losers  as well as differences in incumbent opportunistic behavior in the budgeting year  prior to and during the post-conflict simultaneous local elections held in 2017. Keywords : incumbent opportunistic behavior, post-conflict local elections,  regional income and expenditure budget.